Genome-Based Characterization of Multidrug-Resistant Escherichia coli Isolated from Clinical Bovine Mastitis - dos Santos Alves, Taila; Rosa, Vinícius Sanches; da Silva Leite, Domingos; Guerra, Simony Trevizan [UNESP]; Joaquim, Sâmea Fernandes [UNESP]; Guimarães, Felipe Freitas [UNESP]; de Figueiredo Pantoja, José Carlos [UNESP]; Lucheis, Simoni Baldini [UNESP]; Rall, Vera Lúcia Mores [UNESP]; Hernandes, Rodrigo Tavanelli [UNESP]; Langoni, Helio [UNESP]; Ribeiro, Márcio Garcia [UNESP] (Springer Nature, 2023)
Mastitis occurrence in dairy cows is a broad topic that involves several sectors, from antimicrobial resistance and virulence of strains to economic implications and cattle management practices. Here, we assessed the molecular characterization (antimicrobial resistance determinants, virulence genes, sequences type, serotypes, and plasmid types) of 178 Escherichia coli strains isolated from milk samples from cows with clinical mastitis using a genome-based k-mers approach. Of these, 53 (29.8%) showed multidrug resistance by disc diffusion. We selected eight multidrug-resistant mastitis-associated E. coli for whole-genome sequencing and molecular characterization based on raw data using k-mers. We assessed antimicrobial resistance genes, virulence factors, serotypes, Multilocus Sequence Typing (MLST), and plasmid types. The most antimicrobial resistance gene found were blaTEM-1B (7/8), tetA (6/8), strA (6/8), strB (6/8), and qnrB19 (5/8). A total of 25 virulence factors were detected encoding adhesins, capsule, enzymes/proteins, increased serum survival, hemolysin, colicins, and iron uptake. These virulence factors were associated with Extraintestinal Pathogenic E. coli. Three pandemic clones were found: ST10, ST101, and ST69. Two E. coli were assigned in the O117 serogroup and one in the O8:H25 serotype. The most common plasmid groups were IncFII (7/8) and IncFIB (6/8). Our findings contribute to the knowledge of virulence mechanisms, epidemiological aspects, and antimicrobial resistance determinants of E. coli strains obtained from clinical mammary infections of cows.